Bringing Bioactive Compounds into Membranes: The UbiA Superfamily of Intramembrane Aromatic Prenyltransferases. Issue 4 (April 2016) - Li, Weikai
Abstract : The UbiA superfamily of intramembrane prenyltransferases catalyzes a key biosynthetic step in the production of ubiquinones, menaquinones, plastoquinones, hemes, chlorophylls, vitamin E, and structural lipids. These lipophilic compounds serve as electron and proton carriers for cellular respiration and photosynthesis, as antioxidants to reduce cell damage, and as structural components of microbial cell walls and membranes. This article reviews the biological functions and enzymatic activities of representative members of the superfamily, focusing on the remarkable recent research progress revealing that the UbiA superfamily is centrally implicated in several important physiological processes and human diseases. Because prenyltransferases in this superfamily have distinctive substrate preferences, two recent crystal structures are compared to illuminate the general mechanism for substrate recognition. Trends: Emerging data reveal that the UbiA superfamily of prenyltransferases, including UBIAD1, COQ2, DPPR synthase, and DGGGP synthase, is involved in a wide variety of biological processes and diseases. UBIAD1 catalyzes vitamin K turnover, prevents oxidative damage in cardiovascular tissues, sustains mitochondrial function, and plays a role in lipid metabolism. Dysfunctional UBIAD1 is linked to cardiovascular degeneration, Parkinson's disease, and Schnyder corneal dystrophy. DPPR synthase is required for the formation of M. tuberculosis cell wall and thus is a promising target for anti-tuberculosis drugs. DGGGP synthase is proposed to synthesize the diether and tetraether membrane lipids, key evolutionary features of archaea.